MARITAL QUALITY AND FAMILY TYPOLOGY: EFFECTS ON PAKISTANI ADOLESCENT'S MENTAL HEALTH - Sumaira Rashid (European Scientific Journal, ESJ, 2014)
The present study investigated the influence of quality of marital life and family patterns with adolescents mental health status. The data for the present study was comprised of (n=100) Adolescent and (n = 100) parental couples. The participants belonged to different socioeconomic status with the age range 17 to 19 years. The data was collected from Forman Christian college university, Beaconhouse National University, Hajvery University and university of South Asia through purposive sampling technique. Mental health of adolescents was measured by the mental health inventory and parental marital satisfaction was assessed by Kansas Marital Satisfaction Scale along with Demographic form stating name, age, gender, educational level. Independent t test was employed to analyze results. The findings of the present study showed that there is a significant relationship between parental Marital Satisfaction and Mental health of adolescent. The results also showed that there is a significant difference in mental health of adolescents among joint and nucleus families. Moreover, it was concluded that parental marital satisfaction is better in joint family as compare to nucleus family system.